2008
DOI: 10.1016/j.fuel.2008.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biomass blending on coal ignition and burnout during oxy-fuel combustion

Abstract: Oxy-fuel combustion is a GHG abatement technology in which coal is burned using a mixture of oxygen and recycled flue gas, to obtain a rich stream of CO 2 ready for sequestration. An entrained flow reactor was used in this work to study the ignition and burnout of coals and blends with biomass under oxy-fuel conditions. Mixtures of CO 2 /O 2 of different concentrations were used and compared with air as reference. A worsening of the ignition temperature was detected in CO 2 /O 2 mixtures when the oxygen concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 152 publications
(78 citation statements)
references
References 25 publications
(16 reference statements)
4
73
0
1
Order By: Relevance
“…Any improvement in the burnout of the less reactive component will depend on the oxygen and temperature profiles in the reactor [11]. In this work, olive waste, OW, was more reactive than coals HVN and SAB and so the burnout of the blends was improved.…”
Section: Burnoutmentioning
confidence: 87%
See 3 more Smart Citations
“…Any improvement in the burnout of the less reactive component will depend on the oxygen and temperature profiles in the reactor [11]. In this work, olive waste, OW, was more reactive than coals HVN and SAB and so the burnout of the blends was improved.…”
Section: Burnoutmentioning
confidence: 87%
“…Arias et al [11] observed a substantial reduction in the ignition temperature of coal/biomass blends in air but only a small decrease under oxy-fuel combustion atmospheres. They explained this because biomass has a lower heating value than coal, and so less heat is generated during its oxidation in the ignition process, and CO 2 has a specific heat higher than N 2 .…”
Section: Ignition Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…Lai et al [20] compared the combustion behaviour of lignocellulosic materials in CO 2 /O 2 and N 2 /O 2 atmospheres and calculated the kinetic parameters considering three parallel reactions during the combustion. A few studies have been published on the oxy-fuel combustion of coal and biomass blends [21][22][23], but reactivity and kinetic studies of biomass and coal/biomass blends under oxy-fuel combustion needs to be carried out.…”
Section: Introductionmentioning
confidence: 99%